METHODS OF TEACHING SOCIO-HUMANITARIAN DISCIPLINES - Sodikjon Aminjonovich Asranov (Galaxy International Interdisciplinary Research Journal, 2023)
The purpose of scientific research aimed at the problems of teaching special subjects is to develop methods that increase the effectiveness of teaching and learning, providing practical application in practice, in education, training and learning to solve problems associated with the use of information technology.